MANAGEMENT OF ONLINE DISTANCE LEARNING DURING THE COVID-19 PANDEMIC AT SMPN 1 SAMPIT (STKIP MUHAMMADIYAH SAMPIT, 2022)
The Covid-19 pandemic that was so fierce some time ago caused disruption and even stopped the learning process in the classroom. So that learning is carried out remotely, both online and offline. This situation led the principals to creatively make good practice breakthroughs to keep learning going, even through long distances in the network, as was done at SMPN 1 Sampit The objectives of this good practice focus on: First; How are the efforts to manage distance learning during Covid-19 using diverse applications? Secondly, What are the apps used by teachers during distance learning? The methods used are pre-observation, observation, reflection, action, supervision, and final reflection. The results of this study show that the COVID-19 pandemic has brought good changes in learning management. The management, which was originally in the form of face-to-face meetings, became remote meetings in the network using various applications such as Whatsaap, Si Bajakah, Google Classroom, Edmodo, Zoom Meeting, and Google meet, as well as other applications. The use of this application is quite easy because it has been given training by the school, and the learning process can be achieved according to the goals.